A putative, novel coli surface antigen 8B (CS8B) of enterotoxigenic Escherichia coli - Njoroge, Samuel M.; Boinett, C.J.; Made, L.F.; Ouko, T.T.; Fèvre, Eric M.; Thomson, N.R.; Kariuki, S. (Oxford University Press, 2015)
Enterotoxigenic Escherichia coli (ETEC) strains harbor multiple fimbriae and pili to mediate host colonization, including the type IVb pilus, colonization factor antigen III (CFA/III). Not all colonization factors are well characterized or known in toxin positive ETEC isolates, which may have an impact identifying ETEC isolates based on molecular screening of these biomarkers. We describe a novel coli surface antigen (CS) 8 subtype B (CS8B), a family of CFA/III pilus, in a toxin producing ETEC isolate from a Kenyan collection. In highlighting the existence of this putative CS, we provide the sequence and specific primers, which can be used alongside other ETEC primers previously described.